Impact of Empirical Antimicrobial Treatment on Patients with Ventilator-Associated Pneumonia Due to Stenotrophomonas maltophilia - Pirawan Khunkit; Pisud Siripaitoon; Yongyut Lertsrisatit; Dissaya Watthanapaisal; Narongdet Kositpantawong; Siripen Kanchanasuwan; Nadia Cheh-oh; Sorawit Chittrakarn; Tanapat Jaroenmark; Natnicha Poonchuay; Sarunyou Chusri (Antibiotics, 2024)
This retrospective study was conducted to evaluate the characteristics and outcomes of patients with ventilator-associated pneumonia (VAP) caused by Stenotrophomonas maltophilia (S. maltophilia), focusing on the impact of appropriate empirical antimicrobial treatment. Of the enrolled 240 patients with VAP due to S. maltophilia (median age: 45 years) in a tertiary-care hospital in southern Thailand between January 2010 and December 2021, 90% had medical comorbidities and 91% had previously received carbapenems. In addition, only 45% of the patients were initially admitted to the intensive care unit. Patients administered appropriate empirical antimicrobial treatment including colistin alone and colistin plus TMP-SMX or fluoroquinolone-based regimens had significantly lower 14-day, 30-day, and in-hospital mortalities, compared with those who did not receive appropriate empirical antimicrobial treatment (21% and 2% vs. 31%; 30% and 5% vs. 44%; and 30% and 12% vs. 53%, respectively). Thus, the use of appropriate empirical antimicrobial treatments led to a significantly reduced length of hospital stay, duration of ventilation, and hospital costs. The current study suggests that the use of appropriate empirical antimicrobial treatment based on susceptibility testing without considering pharmacokinetic properties and administration dosages improves the outcomes of patients with VAP due to S. maltophilia.